2011
DOI: 10.1590/s0031-10492011002400001
|View full text |Cite
|
Sign up to set email alerts
|

Maturidade sexual em Callinectes ornatus Ordway, 1863 (crustacea: decapoda: portunidae) no litoral de Ilhéus, BA, Brasil

Abstract: Aiming to estimate the onset of the sexual maturity of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
7
0
4
Order By: Relevance
“…segments (Pinheiro & Fransozo 1993). In some crustaceans, these morphological changes are essential to attain sexual maturity (Petriella & Boschi 1997;Souza-Carvalho et al 2011) and can be revealed by relative growth analysis (Pinheiro & Hattori 2006;Miranda & Mantelatto 2010). In carcinology, this subject is common with species of Brachyuran infraorder (Hartnoll 2001), but a lag is verified with those for Anomuran infraorder, where only a few articles are available about sexual dimorphism (Biagi & Mantelatto 2006;Miranda & Mantelatto 2010;Ferreira 2015).…”
Section: Study Area and Sampling Of Crabsmentioning
confidence: 99%
“…segments (Pinheiro & Fransozo 1993). In some crustaceans, these morphological changes are essential to attain sexual maturity (Petriella & Boschi 1997;Souza-Carvalho et al 2011) and can be revealed by relative growth analysis (Pinheiro & Hattori 2006;Miranda & Mantelatto 2010). In carcinology, this subject is common with species of Brachyuran infraorder (Hartnoll 2001), but a lag is verified with those for Anomuran infraorder, where only a few articles are available about sexual dimorphism (Biagi & Mantelatto 2006;Miranda & Mantelatto 2010;Ferreira 2015).…”
Section: Study Area and Sampling Of Crabsmentioning
confidence: 99%
“…Density-dependent factors, as well as food availability can cause metabolic changes with effects on growth rates, leading to an advance or delay in size at maturity (Wenner et al, 1974;Hines, 1989). Alterations in this variable can also be attributed to the action of different stressors on populations, such as fishing pressure (McQuaid et al, 2006), or result from variations or inaccuracies in the methods employed (Souza-Carvalho et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Apesar da semelhança morfológica entre essas duas fases (jovens e adultos), esses crustáceos também podem por fases larvais e pós-larvais (Bolla Jr et al, 2014), e somente após atingir a maturidade sexual é que se tornam adultos. Esse tamanho pode variar entre as espécies, sendo registrado para: C. ornatus a partir de 40,7 mm largura da carapaça (LC) para fêmeas e 43,5 mm LC para machos (Souza-Carvalho et al, 2011); H. pudibundus a partir de 36 mm LC (fêmeas), 35 mm LC (macho) Branco, 2005) e P. punctata 24,9 mm LC para fêmeas e 27,4 mm LC para machos (Almeida et al, 2013).…”
Section: Caranguejo E Siriunclassified